Pandangan Kenaikan Tarif PPN 12% dengan Menggunakan Sistem Coretax: Implikasi pada UMKM di Indonesia - Anselmus Rufus Kodu; Heri Heri; Roberto Josua F. Hasibuan; Uun Sunarsih (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
Tax is one of the primary sources of government revenue worldwide and is a mandatory contribution to the state without any direct benefit. Among Indonesia's various types of taxes, Value Added Tax (VAT) is one of them. VAT is closely related to taxpayers established as taxable businesses, where VAT is levied on the purchase/sale transactions conducted by individual and corporate taxpayers. On January 1, 2025, the government will increase the VAT rate from 11% to 12%, although this regulation has been met with opposition from various parties. This article discusses the perspectives on the 12% VAT increase using the coretax system. This research employs a qualitative approach through a literature review, involving a review of books, journals, articles, and law-based information related to the research object. The results show that the increase in the VAT rate to 12% has both positive and negative impacts. The positive impact is that it will increase government revenue to be redistributed to the community. Meanwhile, the negative impacts include increased prices of goods/services, rising inflation, and decreased purchasing power of the people.